Survey of Barbell Trajectory and Kinematics of the Snatch Lift from the 2015 World and 2017 Pan-American Weightlifting Championships - Aaron J. Cunanan; W. Guy Hornsby; Mark A. South; Kristina P. Ushakova; Satoshi Mizuguchi; Kimitake Sato; Kyle C. Pierce; Michael H. Stone (MDPI AG, 2020)
Analysis of elite performances is important to elucidate the characteristics of effective weightlifting technique contributing to the highest level of achievement. The general technique of the weightlifting movements is well established. However, it is also apparent that weightlifting technique can differ based on athlete characteristics. Thus, existing technical models may not accurately reflect current technique of top performers or be applied generically to athletes of different skill, size, sex, or ability. Therefore, the purpose of this descriptive study was to update the scientific knowledge of snatch technique of top international weightlifters. This study used video analysis to determine barbell trajectory and kinematics of 319 successful snatch attempts from two major international competitions. Relative frequencies of barbell trajectory types differed based on competition, sex, category, and ranking. No statistical differences were observed among the top-three performers for either sex for most kinematic variables, and there were no overall discernible patterns of effect size differences for individual or clusters of kinematic variables. The results of this study indicate that weightlifting success can be achieved with a variety of technique profiles.